OPERATIONAL COST CONTROL STRATEGY AND BPJS CLAIM OPTIMIZATION ON PERCEIVED FINANCIAL PERFORMANCE OF RSAL RAMELAN SURABAYA IN THE ERA OF UNIVERSAL HEALTH COVERAGE - Zenna Zhahirah Wibowo; Anak Agung Istri Agung Srila Nataswari; Widya Nurjannah; Musdarmawan; Farida Yuliaty (Pena Cendekia Insani, 2026)
This study analyzes the simultaneous effect of operational cost control and BPJS claims optimization on the perceived financial performance of RSAL Ramelan Surabaya in the Universal Health Coverage (UHC) era. Facing financial pressures from high operational costs and claim delays, the hospital requires robust financial strategies. Using a quantitative explanatory approach, data were collected from 102 managerial staff via Likert-scale questionnaires and secondary financial reports. Data were analyzed using SPSS version 31, employing descriptive statistics, classical assumption tests, and multiple linear regression. Results indicate that operational cost control and BPJS claim optimization jointly and significantly predict perceived financial performance. The regressionmodel demonstrates strong explanatory power (Adjusted R2 = 0.927). Due to substantial multicollinearity between the independent variables (V IF = 14.731), findings should be interpreted as evidence of a synergistic association rather than independent causal effects. The study highlights the importance of integrating internal cost-efficiency strategies with BPJS revenue-cycle management to support hospital financial sustainability under Universal Health Coverage. Because the dependent variable reflects managerial perceptions rather than objective financial ratios, future studies should incorporate audited financial indicators and advanced statistical techniques such as Structural Equation Modeling (SEM) or Ridge Regression.